A New Empirical Approach to Intercultural Comparisons of Value Preferences Based on Schwartz’s Theory - Witte, Erich H.; Stanciu, Adrian; Boehnke, Klaus (Frontiers in Psychology, 2020)
Empirical tests of Schwartz’s theory of culture-level value priorities have predominantly been performed using an averaging approach–as values of the average individual in a culture. However, from a theory of measurement standpoint such an approach seems inadequate. We argue that the averaging approach is an insufficiently accurate methodology in capturing the compatibilities-incompatibilities between values of individuals within cultures. We propose an approach based on the distribution of values of individuals in a given culture–the distribution approach. Using data from two rounds of the European Social Survey, we show how frequencies of specific individual value priorities in a culture can be used towards the description of culture-level value preferences. We recommend a re-conceptualization of Schwartz’s culture-level value theory to an orthogonal two-dimensional structure, namely as Preservation vs. Alteration and Dominance vs. Amenability, which we explain based on heterogeneity in socioecological indicators across countries. We conclude that societal challenges may influence the cultural value climate across countries.